Development of a 6Es learning by design based on ESD to enhance concept mastery - Syaiful Rochman; Nuryani Rustaman; Winny Liliawati; Khairul Amri; Taufik Ramlan Ramalis (Universitas Muhammadiyah Malang, 2025)
Mastery of hydrology concepts is essential for future science teachers in addressing sustainability challenges. However, conventional teaching approaches often fail to foster deep understanding and real-world application. This study aimed to develop and implement a 6Es Learning by Design model integrated with Education for Sustainable Development (ESD) to improve prospective science teachers’ mastery of hydrology concepts. A Sequential Exploratory Mixed Methods design was used, involving 28 students enrolled in the Earth and Space Science course. Data were collected through student worksheets, concept mastery tests, and expert validation. Two types of validity—rational and empirical—were employed, and the instrument reliability was assessed using Rasch analysis. Results showed that the developed learning model and materials were highly feasible (100%) based on expert evaluation. Concept mastery improved significantly, with average Rasch score increasing from -0.068 (low) to 1.91 (medium–high) after the intervention. Students actively engaged in designing sustainable hydrology solutions, reflecting the model’s effectiveness in supporting conceptual and contextual learning. The findings suggest that integrating ESD into the 6Es framework strengthens students’ system thinking and problem-solving abilities, offering a promising pedagogical approach for sustainability-oriented science education.